Long-term dry storage of enzyme-based reagents for isothermal nucleic acid amplification in a porous matrix for use in point-of-care diagnostic devices. Issue 21 (21st August 2020) - Kumar, Sujatha; Gallagher, Ryan; Bishop, Josh; Kline, Enos; Buser, Joshua; Lafleur, Lisa; Shah, Kamal; Lutz, Barry; Yager, Paul
Abstract : Long-term dry storage of enzyme-based isothermal amplification reagents in glass fiber porous matrix for use in point-of-care devices. Abstract : Nucleic acid amplification test (NAAT)-based point-of-care (POC) devices are rapidly growing for use in low-resource settings. However, key challenges are the ability to store the enzyme-based reagents in dry form in the device and the long-term stability of those reagents at elevated temperatures, especially where ambient temperatures could be as high as 45 °C. Here, we describe a set of excipients including a combination of trehalose, polyethylene glycol and dextran, and a method for using them that allows long-term dry storage of enzyme-based reagents for an isothermal strand displacement amplification (iSDA) reaction in a porous matrix. Various porous materials, including nitrocellulose, cellulose, and glass fiber, were tested. Co-dried reagents for iSDA always included those that amplified the ldh1 gene in Staphylococcus aureus (a polymerase and a nicking enzyme, 4 primers, dNTPs and a buffer). Reagents also either included a capture probe and a streptavidin-Au label required for lateral flow (LF) detection after amplification, or a fluorescent probe used for real-time detection. The reagents showed the best stability in a glass fiber matrix when stored in the presence of 10% trehalose and 2.5% dextran. The reagents were stable for over a year at ∼22 °C as determined by lateral flow detection and gel electrophoresis. The reagents also exhibited excellent stability after 360 h at 45 °C; the assay still detected as few as 10 copies of ldh1 gene target by lateral flow detection, and 50 copies with real-time fluorescence detection. These results demonstrate the potential for incorporation of amplification reagents in dry form in point-of-care devices for use in a wide range of settings.